Effects of experimental glaucoma in Lama1nmf223 mutant mice. (January 2023) - Madhoun, Salaheddine; Martins, Manuela Tosi Comelis; Korneva, Arina; Johnson, Thomas V.; Kimball, Elizabeth; Quillen, Sarah; Pease, Mary Ellen; Edwards, Malia; Quigley, Harry
Abstract: To identify changes in response to experimental intraocular pressure (IOP) elevation associated with the laminin α1 nmf223 mutation in mice. Laminin mutant (LM) mice ( Lama1 nmf223 ) and C57BL/6J (B6) mice in two age groups each (4–5 months and >1 year) underwent intracameral microbead injections to produce unilaterally elevated IOP. We assessed axonal transport block of immunofluorescently labeled amyloid precursor protein (APP) after 3 days and retinal ganglion cell (RGC) axon loss after 6 weeks. Light, electron and fluorescent microscopy was used to study baseline anatomic differences and effects of 3-day IOP elevation in younger LM mice. In younger mice of both LM and B6 strains, elevated IOP led to increased APP block in the retina, prelaminar optic nerve head (preONH), unmyelinated optic nerve (UON), and myelinated optic nerve (MON). APP blockade not significantly different between younger B6 and LM mouse strains. Older LM mice had greater APP accumulation in both control and glaucoma eyes compared to older B6, however, accumulation was not significantly greater in LM glaucoma eyes compared to LM controls. Axon loss at 6 weeks was 12.2% in younger LM and 18.7% in younger B6 mice (difference between strains, p = 0.22, Mann Whitney test). Untreated LM optic nerve area was lower compared to B6 (nerve area, p < 0.0001, t -test). Aberrant axon bundles, as well as defects, thickening and reduplication of pia mater, were seen in the optic nerves of younger LM mice. Axonal transport blockade significantly differed between old B6 and old LM mice in control and glaucoma eyes, and younger LM mice had abnormal axon paths and lower optic nerve area. Highlights: Lama1 nmf223 mice exhibit defects in the peripheral optic nerve and pia mater. Intra ocular pressure elevation model demonstrated effective transport block. Possible age dependent axonal loss in Lama1 nmf223 mice.